A educação na trajetória intelectual de Arthur Ramos: higiene mental e criança problema (Rio de Janeiro 1934-1949) - Garcia, Ronaldo Aurélio Gimenes (2010)
In this research we look for to critically reconstitute the paper of the education in the intellectual trajectory of Arthur Ramos. This author carried through an intense work of research and developed practical actions throughout its professional and academic experience. Ramos elaborated a theory of psychoanalysis base and humanist who resulted in an important set of concepts, proposals and social intervention that surpassed the limits of the school to reach the family and the community as a whole, extending in such a way the proper concept of education. The intellectual mentioned one was collaborator of Anísio Teixeira in the reform of public education next to the Department of Education of the Federal District during the administration of mayor Pedro Ernesto Batista in the decade of 1930. As part of the reform of Anísio Teixeira the Service of Ortofrenia and Mental Hygiene commanded by Ramos was installed. The objective to receive the children who were considered as incapable to learn and who presented a misadjusted behavior directed from the public school. It enters the objectives of the present research we can detach: to present Arthur Ramos as an intellectual of its time, involved with the controversies of its time in the interior of the field and thinking about forms of overcoming of the educational and social quandaries of the nation under the prism of the humanism and the democracy; to analyze its pedagogical proposals and of intervention in the school by means of the mental hygiene; to referential the child concept problem and to analyze its workmanship of scientific spreading Spirit Health of the 1939. The reverential theoretician methodology had been used the patrimonialism concepts, of authoritarian modernization, of intellectual field and habitus. The developed research search to use of the analysis of the intellectual production and the practical politics of Arthur Ramos from some documentary sources as published workmanships, periodic and manual assays, scientific articles in of spreading. Everything indicates that the proposals of Arthur Ramos were beyond the historical possibilities of the decades of 1930 and 1940. The work of the alagoano doctor of undeniable pioneers in the field of the applied psychoanalysis and the anthropology to the education was not enough to hinder that its accomplishments were condemned to the intellectual ostracism the one that had been deliver during many decades. The rescue of the thought and the practical one of Ramos is a form to retake the memory intellectual of that historical period especially of the field of the knowledge of the history of the education.